Summer of my German soldier - Greene, Bette, 1934- (New York : Dell Pub., 1993)
Sheltering an escaped German prisoner of war is the beginning of some shattering experiences for a twelve-year-old Jewish girl in Arkansas.
Originally published: New York : Bantam Books, c1973.
"Laurel-Leaf Books."
3 4 10 13 27 32
Keywords: Jews -- United States -- Fiction; Prisoners of war -- Fiction; Prejudices -- Fiction